Fixed Point Results for Geraghty Type Generalized F-contraction for Weak alpha-admissible Mapping in Metric-like Spaces (European Journal of Pure and Applied Mathematics, 2018)
In this paper, we establish the existence of some fixed point results for generalized(Alpha,Beta,F)-Geraghty contraction in metric-like spaces. We provide an example in order to supportÂ our results where some consequence applications of such result will be considered in this article. TheÂ obtained results improve and extend some well-known common fixed point results in the literature.